Effect of maternal polycystic ovary syndrome (PCOS) on screening of aneuploidy in the first and second trimesters - Narjes Hassan Haivadi; Shahideh Jahanian Sadatmahalleh; Fatemeh Razavinia; Sarang Younesi; Malihe Nasiri; Saeideh Ziaei (BMC, 2023)
Abstract Background Polycystic ovary syndrome (PCOS) is characterized by insulin resistance and hormonal disorder in women. This study aimed to assess the effect of maternal PCOS on screening of aneuploidy in the first and second-trimesters. Methods This case-control study was conducted in Arash Hospital and Nilou Laboratory in 2017-2018. The screening test was conducted on 90 PCOS and 90 healthy mothers. Finally, the first and second-trimester screening was compared between the two groups using Chi-square, Mann-Whitney's U and students T tests and regression model by SPSS 21. P < 0.05 was considered as statistically significant. Results Free Beta-Human Chorionic Gonadotropin (Free-β-HCG) (P = 0.04), inhibin-A (P = 0.001) and Alpha Fetoprotein (AFP) (P = 0.02) levels were higher in the PCOS women comparing to the healthy women but there was no significant difference between the mean of HCG, Plasma Protein A (PAPP-A), and Unconjugated Estriol (UE3) between the two groups. Pre-eclampsia (P < 0.001) and trisomy 18 risks in quad screening were higher in the PCOS women (P = 0.002) than the control group; however, trisomy 13, trisomy 18 and trisomy 21 risks, Smith-Lemli-Opitz Syndrome (SLOS) and Neural Tube Defect (NTD) risks were not different between the two groups. The logistic regression model showed that the first- and second-trimester screening of aneuploidywas related to PCOS. Conclusions There was a significant difference in the mean of free-β-HCG, inhibin-A, AFP level, and the risks of pre-eclampsia, SLOS and trisomy 18 between the two groups but no significant association was found in the mean of HCG, PAPP-A, UE3, NTD and other aneuploidies between the two groups. PCOS may affect the first- and second-trimester screening tests and pregnancy health. It may also require correction in the calculation of risks related to the first- and second-trimester screening for aneuploidy.